Complications of CSF Shunting in Hydrocephalus : Prevention, Identification, and Management - Di Rocco, Concezio; Turgut, Mehmet; Jallo, George; Martínez-Lage, Juan F. (Springer International Publishing : Imprint: Springer, 2015)
Written and edited by leading international authorities in the field, this book provides an in-depth review of knowledge of complications of CSF shunting, with emphasis on prevention, identification, and management. It covers the full range of shunt-related complications and the various associated adverse consequences that remain common despite significant improvements in imaging techniques and therapeutic methods. The chapters are organized into three parts: introduction, complications of extrathecal CSF shunt devices, and complications of endoscopy. In addition to providing clinicians and investigators with the most pertinent current evidence, the book looks forward to future areas of hydrocephalus research and to innovative therapeutic philosophies. This comprehensive reference book will be an ideal source for neurosurgeons seeking both basic and more sophisticated information and procedures relating to the complications associated with CSF shunting. It will also contribute in overcoming the problem of lack of knowledge of basic fluid dynamics and workings of the shunts - knowledge that is essential for optimal care of hydrocephalic patients. .